Legal Aspects of Banking in Protecting Workers' Rights: An Analysis of the Interconnection Between Banking and Labor Regulations - Dalimunthe, Nikmah; Athariq, Difa (International Journal Of Education, Social Studies, And Management (IJESSM), 2024)
This study aims to analyze the relationship between banking and employment regulations in protecting labor rights in Indonesia. Using a literature study method, this study examines legal documents such as Law Number 13 of 2003 concerning Employment, the Banking Law, Financial Services Authority Regulations (POJK), and Bank Indonesia Regulations (PBI), as well as relevant academic literature. Descriptive-analytical analysis was conducted to evaluate the suitability of regulations with banking operational practices and identify potential synergies between regulations to strengthen the protection of labor rights. The results of the study indicate that there are regulatory gaps that require harmonization to ensure banking compliance in supporting workers' rights, especially related to the management of welfare funds and the fulfillment of labor obligations. This study recommends strengthening coordination between banking and labor regulators to create a more integrated and effective legal framework.